2013
DOI: 10.1007/s00345-013-1139-7
|View full text |Cite
|
Sign up to set email alerts
|

Is larger tumor size a contraindication to retroperitoneal laparoscopic adrenalectomy?

Abstract: Retroperitoneal laparoscopic adrenalectomy can be used in patients with tumors larger than 5 cm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 22 publications
3
19
0
Order By: Relevance
“…7,8,21 However, a comparison between LA using the lateral retroperitoneal approach and other surgical approaches has rarely been reported. 10,25 Although the anatomical orientation of the retroperitoneoscopic technique might be more difficult using a lateral rather than posterior approach, it could result in shorter operating time with favorable outcomes when carried out by experienced surgeons after a certain learning curve. 25 When retroperitoneoscopic adrenalectomy is carried out for PCC, patients with a posterior approach seemed to have a greater incidence of intraoperative risks than those with a lateral approach, owing to the following reasons: (i) the patient's position on the operative table itself could directly cause hemodynamic instability; 26 (ii) it is not easy to rapidly convert the procedure into an open technique in the case of major bleeding; 27 and (iii) in patients with a high BMI, the adipose tissue raises intra-abdominal pressure in the dorsal position, and the retroperitoneal space is highly compressed because of the presence of excess adipose tissue.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…7,8,21 However, a comparison between LA using the lateral retroperitoneal approach and other surgical approaches has rarely been reported. 10,25 Although the anatomical orientation of the retroperitoneoscopic technique might be more difficult using a lateral rather than posterior approach, it could result in shorter operating time with favorable outcomes when carried out by experienced surgeons after a certain learning curve. 25 When retroperitoneoscopic adrenalectomy is carried out for PCC, patients with a posterior approach seemed to have a greater incidence of intraoperative risks than those with a lateral approach, owing to the following reasons: (i) the patient's position on the operative table itself could directly cause hemodynamic instability; 26 (ii) it is not easy to rapidly convert the procedure into an open technique in the case of major bleeding; 27 and (iii) in patients with a high BMI, the adipose tissue raises intra-abdominal pressure in the dorsal position, and the retroperitoneal space is highly compressed because of the presence of excess adipose tissue.…”
Section: Resultsmentioning
confidence: 99%
“…22 Additionally, it effectively minimizes postoperative blood loss because of the small space of the retroperitoneum. 10 Early adrenal vein ligation before tumor manipulation is beneficial in patients with PCC to reduce the risk of excessive catecholamine secretion and cardiovascular complications. 11,23 Based on the present results, the large tumor group showed a longer operating time and greater quantities of blood loss with significant changes in hemoglobin levels compared with those belonging to the small tumor group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with those in a previous study in which patients with large adrenal tumors (8 cm) underwent LTA, the operative time and hospitalization time were longer and the blood loss was greater, but complications such as conversion to OA and blood transfusion were reduced (Table ) . Moreover, Insang et al evaluated the surgical feasibility of RLA for tumors ≧5 cm and found that the operative time, estimated blood loss, postoperative hospital stay, transfusion, and surgical complications were 214.54 ± 76.04 min, 367.24 ± 275.11 mL, 9.26 ± 3.10 d, 6 (7.9%), and 13 (17.1%) respectively, for large adrenal tumors (7.10 ± 2.15 cm) (Table ) . Compared with traditional RLA, transient renal artery occlusion decreased the operative time, blood loss and complications and accelerated postoperative rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several studies comparing retroperitoneal laparoscopic adrenalectomy (RLA) and LTA have suggested that the RLA outcomes were superior to those of LTA, specifically the shorter surgery duration, reduced blood loss, lower postoperative pain, faster recovery, decreased length of hospital stay, improved cost‐effectiveness, and abolished risk of surgical access site herniation . However, the estimated blood loss, time to ambulation, and postoperative hospitalization were significantly higher in patients with tumors larger than 5 cm than in patients with tumors smaller than 5 cm . Magda et al indicated that RLA was the most advantageous approach in cases with tumors less than 7 cm in diameter in a comparative study between RLA and LTA, and a recent systematic review showed that RLA seemed to be superior to LTA in terms of operative time, duration of hospitalization and postoperative pain, with a comparable incidence of peri‐ and postoperative complications, especially in masses <8 cm .…”
Section: Introductionmentioning
confidence: 99%